Test of lepton flavor universality in semileptonic (Formula presented) meson decays in proton-proton collisions at (Formula presented) - Hayrapetyan,A; Tumasyan,A; Adam,W; Andrejkovic,JW; Bergauer,T; Chatterjee,S; Damanakis,K; Dragicevic,M; Hussain,PS; Jeitler,M; Krammer,N; Li,A; et al. (Physical Review D, 2025)
A measurement of the ratio of branching fractions (Formula presented) in the (Formula presented), (Formula presented) decay channel is presented. This measurement uses a sample of proton-proton collision data collected at a center-of-mass energy of (Formula presented) by the CMS experiment in 2018, corresponding to an integrated luminosity of (Formula presented). The measured ratio, (Formula presented), agrees with the value of (Formula presented) predicted by the standard model, which assumes lepton flavor universality. By testing lepton flavor universality, this measurement is a probe of new physics using (Formula presented) mesons, which are currently only produced at the LHC.